2019
DOI: 10.15622/sp.18.1.85-122
|View full text |Cite
|
Sign up to set email alerts
|

Features of solving the inverse dynamic method equations for the synthesis of stable walking robots controlled motion

Abstract: The problem of walking robots controlled motion synthesis by the inverse dynamic method is considered. The inverse dynamic method equations are represented by the methods of multibody system dynamics as free bodies motion equations and constraint equations. The variety of constraint equations group are introduced to specify the robot gait, to implement the robot stability conditions and to coordinate specified robot links movement. The key feature of the inverse dynamic method equations in this formulation is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It was experimentally confirmed that successful gripping without deformations, displacements and slipping with optimal values of accuracy parameters was achieved in 97% of cases. The proposed solution with some adjustments in the implementation of the algorithm structure is applicable for the implementation of the gait of walking and anthropomorphic robots, as well as to determine the control operations of pedipulators [26].…”
Section: Discussionmentioning
confidence: 99%
“…It was experimentally confirmed that successful gripping without deformations, displacements and slipping with optimal values of accuracy parameters was achieved in 97% of cases. The proposed solution with some adjustments in the implementation of the algorithm structure is applicable for the implementation of the gait of walking and anthropomorphic robots, as well as to determine the control operations of pedipulators [26].…”
Section: Discussionmentioning
confidence: 99%
“…Consider the flat inverted double pendulum shown in Figure 1. These pendulums are often considered in problems of control synthesis of walking robots [21][22][23][24][25][26][27][28][29][30][31][32]. The limit on the magnitude of the torque in the pendulum support is a condition for the stability of the robot (i.e., avoiding overturning).…”
Section: Inverted Double Pendulummentioning
confidence: 99%
“…Based on the analysis performed, as well as the data presented in the works [16][17][18], the time for obtaining data from the sensors and calculating the center of applied pressure area to the foot should be in the range of up to 10 ms for the robot's control system to respond sufficiently and to create a stable gait.…”
Section: Introductionmentioning
confidence: 99%